The First Language Interference in Producing English Consonant Sounds - Kurniawati, Layla (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
Peer teaching is a learning approach whichis developed for developing student’s English reading skillat IPDN. This research is designed to solve some problemsin teaching English at three curriculum systems at IPDN,especially English teaching problems at parentingcurriculum system. This research explores the concept ofpeer teaching approach which utilizes peers in the form ofinteraction among the same level students and also in theform of junior and senior students who are moreknowledge of English. This research focus on thecollaboration among students, lecturers, trainers andother staffs for solving English teaching problems atIPDN. The method is mix methods (qualitativequantitative). The qualitative step is conducted by needanalysis (the strength, weaknesses, opportunities and alsothe threat belong to IPDN). The data are collected in theforms of documents, observations and interviews. Theoffering teaching approach tested in limited and extensivegroup. The results show that the pre-test score hasincrease at post test score consecutively. from 51.78 whenthe pre-test became 59.55, the first post-test, 75.11 at thesecond post-test, and 81.33 at the 3rd post test, at limitedand extensive test. The other results are the developmentof the students reading and speaking skills, the increase ofstudent’s interest of learning English, the embryo oflearning community among the students, teachers,trainers, staffs of IPDN. The requirements for planningthe activities before being applied to real classes are also aprerequisite for making learning in large classesapplicable.